2010
DOI: 10.1093/jaoac/93.2.516
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Tadalafil in Pure Powder and Tablet Dosage Form by High-Performance Liquid Chromatography

Abstract: A simple and accurate method to determine tadalafil (TAD) in pure powder and tablet dosage form was developed and validated using HPLC. The separation was achieved on an Xterra RP18 column (150 4.6 mm id, 3.5 m) in the isocratic mode using bufferacetonitrile (70 + 30, v/v), adjusted to pH 7.00 0.05 with triethylamine as the mobile phase at a flow rate of 1.0 mL/min. The photodiode array detector was set at 225 nm. Quantification was achieved over the concentration range of 50.7152.10 g/mL with mean recovery of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Analysis of Tadalafil from pharmaceutical preparations using UV spectrophotometry [17][18][19][20][21][22][23][24][25][26] and 1 th Degree Derivative Spectrophotometry [27,28] are reported in the literature as spectroscopic analysis. In terms of chromatographic analysis; HPLC determinations from food and conventional pharmaceutics [29][30][31][32][33][34] , from human plasma and serum [35,38] and from pharmaceutics [37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53] are also took place. To the authors' knowledge, experimental pKa values for CAB and TAD are not reported in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of Tadalafil from pharmaceutical preparations using UV spectrophotometry [17][18][19][20][21][22][23][24][25][26] and 1 th Degree Derivative Spectrophotometry [27,28] are reported in the literature as spectroscopic analysis. In terms of chromatographic analysis; HPLC determinations from food and conventional pharmaceutics [29][30][31][32][33][34] , from human plasma and serum [35,38] and from pharmaceutics [37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53] are also took place. To the authors' knowledge, experimental pKa values for CAB and TAD are not reported in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Few reports for the determination of VARD in pure, tablet dosage forms and biological fluids have been developed with the help of a variety of analytical tools including high performance liquid chromatography (HPLC) [3][4][5][6][7][8][9][10][11][12] , gas chromatography 13,14 , capillary electrophoresis 15,16 , electrochemical methods 17,18 and atomic emission spectrometry [19][20][21] . Several analytical methods have been reported for the estimation of TDF in biological fluids or pharmaceutical dosage forms include HPLC [22][23][24][25][26][27][28][29][30][31][32][33][34] , liquid chromatography-tandem mass spectrometry with electrospray ionization [35][36][37] , micellar electro kinetic capillary chromatography 38 and atomic emission spectrometry 20,21 .…”
Section: Introductionmentioning
confidence: 99%
“…The chemical structure of vardenafil HCl (VARD) and tadalafil (TDF) Few reports for the determination of VARD in pure, tablet dosage forms and biological fluids have been developed with the help of a variety of analytical tools including high performance liquid chromatography (HPLC) [3][4][5][6][7][8][9][10][11][12] , gas chromatography 13,14 , capillary electrophoresis 15,16 , electrochemical methods 17,18 and atomic emission spectrometry [19][20][21] . Several analytical methods have been reported for the estimation of TDF in biological fluids or pharmaceutical dosage forms include HPLC [22][23][24][25][26][27][28][29][30][31][32][33][34] , liquid chromatography-tandem mass spectrometry with electrospray ionization [35][36][37] , micellar electrokinetic capillary chromatography 38 and atomic emission spectrometry 20,21 .…”
Section: Introductionmentioning
confidence: 99%